2017
DOI: 10.1097/nne.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curriculum Revision on Graduates' Transition to Practice

Abstract: The effect of educational interventions on the transition experiences of new graduates of prelicensure programs is unclear. This study investigated the effect of curriculum revision on transition to practice of nursing graduates. The nursing curriculum can have a positive influence on professional and job satisfaction at 3 months postgraduation, but the practice environment becomes the dominant force after that. Graduates who demonstrated poorer transition to practice at 3 months were more likely to leave thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
2
13
0
5
Order By: Relevance
“…This higher dissatisfaction in graduate nurses in contrast with students was also found by Milton-Wildey et al [23] and Günay and Kilinç [14]. Work readiness is an area of concern still under research in our field and our findings echoed those of Meyer et al [24] and Milton-Wildey et al [23] in that nurses felt unprepared to enter working life. In a recent review [25], it was clearly highlighted that the educational factor is one of the most important contributors to work readiness.…”
Section: Discussionsupporting
confidence: 87%
“…This higher dissatisfaction in graduate nurses in contrast with students was also found by Milton-Wildey et al [23] and Günay and Kilinç [14]. Work readiness is an area of concern still under research in our field and our findings echoed those of Meyer et al [24] and Milton-Wildey et al [23] in that nurses felt unprepared to enter working life. In a recent review [25], it was clearly highlighted that the educational factor is one of the most important contributors to work readiness.…”
Section: Discussionsupporting
confidence: 87%
“…A great current questioning among professional education scholars is that if we really want to transform nursing education and practice, we must believe and find proposals to implement the positive results of educational strategies directed to the environment of practice 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a narrative way, they describe the competencies that must be repeatedly demonstrated during curricular schedules in clinical environments with different levels of complexity 14 , allowing the possibility of a feedback to stimulate changes in observed behaviors, as well as a greater precision in the application of evaluative scales 15 - 17 . Competency frameworks have been expanded in varied medical specialties such as General Surgery 12 , 18 - 19 , Pediatrics 20 - 22 , Urology 23 , and specially Emergency 13 , 17 , 23 - 27 , in which worldwide advances in multiprofessional care occur 28 . In nursing training, however, competency frameworks represent a topic yet to be explored, because the content taught often depends on the teachers’ conceptions and does not have a specific discipline to be approached 29 .…”
Section: Introductionmentioning
confidence: 99%
“…All experimental studies (Lee et al 2009; Meyer et al 2017; Tseng et al 2013) were pre-post intervention so most CASP criteria did not apply and none had blinding of participants. Lee et al (2009) showed a reduction in turnover as a result of a preceptorship programme and provided a cost analysis and the effect on medication errors; both were reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al (2009) showed a reduction in turnover as a result of a preceptorship programme and provided a cost analysis and the effect on medication errors; both were reduced. Meyer et al (2017) and Tseng at al (2013) both showed reduced job changing in the intervention group which had experienced a revised curriculum before qualifying (Meyer et al 2017) and a practicum at the end of their courses was based on collaboration between their schools and their hospitals and a jointly developed programme (Tseng et al 2013).…”
Section: Resultsmentioning
confidence: 99%